Formulation and evaluation of lip balm preparations of ethanolic extract from beetroot (Beta vulgaris L.) - Hadi, Ismanurrahman; Shinta, Tiara Aries; Putra, Teguh Adiyas (Universitas Muhammadiyah Yogyakarta, 2025)
Beetroot (Beta vulgaris L.) is a source of betacyanin that could be used as a natural dye and is known as an antioxidant that can protect the skin from exposure to free radicals. Lip balm, one of the popular cosmetics, often uses natural ingredients as active compounds to enhance colour and promote healthy skin. This study aims to formulate beetroot ethanolic extract into a topical lip balm preparation. The beetroot was extracted using ethanol solvent. The phytochemical screening was carried out to identify phytochemicals of flavonoids, saponins, tannins, and alkaloids within the ethanolic extract. The extract was formulated into a lip balm preparation with extract concentrations of 0% (F1), 5% (F2), 10% (F3), and 15% (F4). After formulation, the lip balm was physically examined for organoleptic, homogeneity, acidity, spreadability, and adhesivity of the product. The phytochemical screening exhibited positive results in all phytochemical groups tested in the beetroot ethanolic extract. Meanwhile, physical evaluation of lip balm demonstrates that all formulations had a semi-solid texture, cacao scent, and red color that increased in intensity proportionate with the extracts used (F2, F3, F4). Other parameters indicate a homogeneous product with suitable acidity (pH valued at 9) and adhesivity (>4 seconds). However, the spreadability test displayed low dispersion capabilities of the lip balm. Even though the spreadability values increased with higher beetroot extract, this value remained lower than the standard minimum dispersion of lip balm, thus indicating poor spreadability of the formula. The hedonic evaluation indicates that respondents tended to like the third formulation (F3). Based on this, the best and most preferred formula is at a concentration of 10% active substance (F3).